2020
DOI: 10.7717/peerj.8312
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a three-gene signature as a candidate prognostic biomarker for lower grade glioma

Abstract: Background Lower grade glioma (LGG) are a heterogeneous tumor that may develop into high-grade malignant glioma seriously shortens patient survival time. The clinical prognostic biomarker of lower-grade glioma is still lacking. The aim of our study is to explore novel biomarkers for LGG that contribute to distinguish potential malignancy in low-grade glioma, to guide clinical adoption of more rational and effective treatments. Methods The RNA-seq data for LGG was downloaded from UCSC Xena and the Chinese Gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
6
19
0
Order By: Relevance
“…It is highly expressed in normal human lung tissues (Ballard et al, 2010) and poorly expressed in LUAD tissues. Patients with LUAD, BLCA and LGG with low expression of CRTAC1 have poor prognosis, which is consistent with that found in glioma (Xiao et al, 2020). Cytochrome P450 4B1 (CYP4B1) is a tissue-specific detoxification-related monooxygenase and is down-expressed in LUAD, but its role in tumorigenesis is still unclear (Lim et al, 2020;Ni and Sun, 2019).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It is highly expressed in normal human lung tissues (Ballard et al, 2010) and poorly expressed in LUAD tissues. Patients with LUAD, BLCA and LGG with low expression of CRTAC1 have poor prognosis, which is consistent with that found in glioma (Xiao et al, 2020). Cytochrome P450 4B1 (CYP4B1) is a tissue-specific detoxification-related monooxygenase and is down-expressed in LUAD, but its role in tumorigenesis is still unclear (Lim et al, 2020;Ni and Sun, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…Gene expression profile array could be used to identify differentially expressed genes (DEGs) between tumor samples and normal samples (Dong et al, 2020), and some key genes can be identified by bioinformatics mining (Xiao et al, 2020). However, integrating the contributions of several key genes to improve the accuracy and the sensitivity of tumor prognosis judgment has always been a difficult problem in its clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of WEE1 has been found to be associated with poor prognosis in a variety of tumor types including gliomas [25]. Two other gene signatures constructed to predict the prognosis of LGG are also consistent with the results of this article, and found that WEE1 is a prognostic risk factor [26,27]. H2B clustered histone 12(H2BC12 or HIST1H2BK) is a replication-dependent histone and belongs to the histone H2B family.…”
Section: Discussionsupporting
confidence: 84%
“…This observation is supported by other studies who have found a clear relation between mitochondrial genomic alterations and BCR (Ellinger et al, 2008;Kalsbeek et al, 2016;Xu et al, 2020). This is not the first time that predictive three-genes signatures have been identified in various diseases (Sun et al, 2015;Thakkar et al, 2015;De Palma et al, 2016;Ibrahim et al, 2016;Wang et al, 2016;Li et al, 2017;Chen et al, 2018;Yang et al, 2018;Bao et al, 2019;Ding et al, 2019;Saidak et al, 2019;Xiao et al, 2020), hence showing that extensive research is ongoing The omics model is based on three genes and the clinic model is a model based on the grade, stage and PSA. The omics + clinic model integrates all the selected features together.…”
Section: Discussionsupporting
confidence: 65%